Global burden of osteoarthritis among postmenopausal women in 204 countries and territories: a systematic analysis for the Global Burden of Disease Study 2021 - Jing Wang; Chenggang Jin; Lingling Sun; Lilu Ding; Dan Zhou; Yingjun Li; Wenfeng Xiao; Huadong Xu; Chan Ding; Jiarong Zou (BMJ Global Health)
Objectives Our study aimed to provide global burden and temporal trends in the incidence, prevalence, and disability-adjusted life-years (DALYs) of osteoarthritis (OA) among postmenopausal women from 1990 to 2021.Methods The study employed data from the Global Burden of Disease (GBD) Study 2021. Four subtypes of OA affecting the hip, knee, hand, and other joints among postmenopausal women were included. Age-standardised rates (ASRs) were derived with reference to the global age standard, and temporal patterns were scrutinised through estimated annual percentage change (EAPC) assessments. The impact of age, body mass index (BMI), and Socio-demographic Index (SDI) were all considered.Results From 1990 to 2021, there were more than 1.3-fold increases in OA incidence, prevalence, and DALYs among postmenopausal women globally, with EAPCs of 0.211, 0.356, and 0.395, respectively. Knee OA carried the heaviest burden, while hip OA bore the least. Higher SDI regions had higher burden, and inequalities linked to SDI among countries had intensified over time. East Asia and high-income Asia Pacific experienced the most substantial increments in OA burden. High BMI significantly influences the burden of OA, especially in countries within high, high-middle, and middle SDI, where DALYs attributed to high BMI exceed 20%.Conclusions The burden of OA among postmenopausal women continues to escalate, highlighting its significant impact on the global health of postmenopausal women. Necessarily, effective monitoring and management of risk factors, targeted lifestyle adjustments for BMI, and policy interventions accounting for demographic disparities are required to ease OA in postmenopausal women.